PENEGAKAN HUKUM TERHADAP PERTAMBANGAN EMAS TANPA IZIN (PETI) SEBAGAI UPAYA PENGENDALIAN DAMPAK LINGKUNGAN DI KECAMATAN SINTANG KABUPATEN SINTANG - Suhendra, Arya; Kamarullah, Kamarullah; Nafsiatun, Nafsiatun (Universitas Lambung Mangkurat, 2023)
Gold mining without a permit is one of the activities that results in a decrease in environmental quality, because gold mining activities use mercury to separate gold ore from rocks until the refining process. The purpose of this study is to identify and analyze the implementation of law enforcement against gold mining without a permit and controlling the environmental impact of gold mining without a permit in Sintang District, Sintang Regency. The type of research is sociological juridical. Data collection by interview and observation was then analyzed by qualitative methods. Unlicensed gold mining is caused by economic factors, education and the community feels they have the right to manage natural resources. Gold mining law enforcement without a permit applies criminal law with the imposition of fines and is still not optimal due to several constraints on the location of miners moving around, the absence of regional regulations related to PETI and community resistance. The government's efforts to control environmental impacts on water pollution from PETI activities are monitoring water quality conditions on a regular basis.